Rafflesia kemumu (Rafflesiaceae), a new species from Northern Bengkulu, Sumatra, Indonesia - Susatya, Agus; Hidayati, Siti Nur; Riki, Septian (Phytotaxa, 2017)
Rafflesia kemumu is a new species described from Northern Bengkulu in Sumatra, Indonesia. The species resembles R. gadutensis in size of the open flower, but differs from it with regard to the color and wart ornamentation on the upper surface of the perigone lobes, color and presence/absence of warts on the upper surface of the diaphragm, blots pattern on the two concentric rings of windows near the diaphragm opening, types and distribution of ramenta, number and shapes of processes, and number of anthers. The new species has orange to dark orange perigone lobes with warts of two sizes, in which smaller warts are often merged, and surround larger ones, and 23 slender, conical processes with rounded apex, arranged in two concentric rings (15 and 7 processes each) and a single process in the center of the disc. Rafflesia kemumu has no warts at its upper surface of diaphragm, simple and compound toadstool ramenta on its upper perigone tube and the lower part of the lower surface of its diaphragm and broccoli-like ramenta distributed from the base to the upper part of the perigone tube.